TRI HITA KARANA AND HYDROLIC CYCLE BASED ON VEDA - Sri Yudari, A.A. Kade; Suarka, I Nyoman; Kutha Ratna, I Nyoman; Weda Kusuma, I Nyoman (e-Journal of Linguistics, 2016)
Hydrologic cycle refers to the route of water cycle or the journey made by water on the earth’s surface. Water can change in form, and flows in various places before finally it gets back to the biggest source, that is, the ocean. Approximately 71% of the earth is covered with the ocean. Talking about the hydrologic cycle cannot be separated from talking about the sun and the ocean, that is, the impact of the rise and fall of the tides. In Veda, the traditional geography, in general, and in Tatwa and Purana , in particular, it is stated that the earth is divided into two parts; they are the main land and the ocean. The question is how deep the Hindu theology and philosophy about the hydrologic cycle is. The water on the earth’s surface evaporates, resulting from the hot ray radiated by the sun. In Reg. Veda Samhita.I.164.51, it is strongly stated that “the water on the earth’s surface rises due to evaporation”. After evaporation, water changes into water drops or fine dews referred to as clouds. There are many types and forms of clouds which may lead to storms; however, some have no impact. When such clouds are already formed, they are brought to every area of the earth’s surface. When they reach the saturation point, a natural phenomenon appears which is referred to as rain. The falling water makes the earth wet, fills up dams, flows along rivers, and fertilize every type of life on earth. Rain measures how the hydrologic cycle takes place. Therefore, it should be recognized that it is important to maintain the hydrologic cycle, which determines that the earth’s fertility and prosperity will not be disturbed. The Hindu teaching is rich in such a philosophy referred to as Tri Hita Karana . Even in very religious ritual water is always mainly used for purification. The sources of water such as wells, rivers, lakes, showers, and oceans are made to be physically and spiritually sacred. The concepts of balance and harmony are easily found in rituals and the philosophy of Veda, the holy book. Almost all the Hindu rituals and philosophies refer to the balanced and harmonious nature. The Hindu philosophy that it is important to protect water for all the creatures on the earth’s surface can guarantee the life sustainability. The life of every creature cannot be separated from water. If the hydrologic cycle which supports every life on earth is damaged, then the human life on earth will be damaged as well.
Keywords: Hydrologic Cycle, Veda, Tri Hita Karana